Characterization of Little millet (Panicum sumatrense) varieties using Morphological descriptors and SSR based DNA fingerprinting - Natesan, Senthil; Venugopalan, Gayathri; Selvamani, Selva Babu; krishnamoorthy, Madhumitha; Chandran, Sarankumar; Angamuthu, Nirmalakumari (Journal of Phytology, 2020)
Little millet varieties are generally distinguished by morphological descriptors which are being used for seed certification and DUS characterization [1]. But in practical terms, these key differentiation descriptors between varieties of little millet are very fewer and hence difficult to differentiate germplasm accessions. Germplasm registration in NBPGR needs DNA fingerprint to show the uniqueness of germplasm in comparison to existing varieties. DNA fingerprinting is a better option to identify unique markers to differentiate the varieties. Available genomic resources are scarce since little millet is still considered to be an orphan crop. Therefore markers from other cereal genomes such as maize, pearl millet and barnyard millet that are been utilized for DNA fingerprinting purpose with a clue of cereal synteny relationship. Twenty-one morphological descriptors studies revealed that the variety ATL 1 is different from the other varieties for more than 16 morphological characters studied. DNA fingerprinting is attempted in five genotypes of little millets such as BL6, ATL 1, TNPsu 176, Co (Samai) 4, Paiyur 2 using cereal SSR markers. Among the 25 maize SSR markers used two markers viz., phi213984 and phi295450 scored polymorphism by the amplicon size of 310bp and 600bp respectively. From the 25 Pearl millet SSR markers used only one SSR marker found polymorphic at 305bp allele size for ATL 1 and Hence, SSR based DNA fingerprinting helped to differentiate ATL1, the newly released high yielding variety from other genotypes of little millets which can be used for varietal identification purpose.